Training and Human Resource Development at the Indonesian School Kuala Lumpur (SIKL) through the International Partnership Community Service Program (PPM KI) - Moh Septian S. Anwar; Suleman Faqih Al Waly; Dani Kurniawan (International Conference on Education for All, 2023)
The tridharma of higher education consists of three obligations that must be carried out within higher education institutions. These three obligations consist of 3 points, namely Education and Teaching, Research and Development, and Community Service. To realize the Tridharma of Higher Education, one of them includes a community service program (PPM) that must be implemented by all students. Students who undertake the Community Service Program (PPM) in International Partnerships (KI) or KKI (International Partnership Community Service) are expected to be able to apply the knowledge they have acquired in their academic studies within the community. This program is a community service activity aimed at improving the quality of service, in collaboration with higher education institutions/academics/LSM activists/PCIM outside the country. The target of this service is Indonesian citizens or Indonesian community abroad. Each student will be integrated and collaborate with participants from other HEIs (Higher Education Institutions) with varying numbers as needed in each SB (Community Service Site). One of them is the Pantai Dalam Guidance Center. The results of this KKN/PPM KI activity are expected to produce independent programs that we collectively create. The main work program includes eradicating Quranic illiteracy (BTA), strengthening the interests and talents of students, strengthening the character of students, and implementing AIK (Religious and Faith Education), which are also part of the programs that we prioritize.